2013
DOI: 10.5414/cp201833
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a relationship between the serum concentration of aminoglycosides and ototoxicity in neonates

Abstract: Our study indicated that there was no relationship between aminoglycosides serum trough concentration and ototoxicity in neonates with neonatal sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Two risk factors were examined in isolation due to their high frequency of occurrence and known association or equivocal association with hearing loss. One of these factors was treatment with ototoxic medications due to the incongruous findings between hearing loss and ototoxic medications in previous studies (e.g., no association found by Hess et al, 1998, andSetiabudy et al, 2013; association found by Bielecki, Horbulewicz, & Wolan, 2011;Fuchs et al, 2016;Robertson, Tyebkhan, Peliowski, Etches, & Cheung, 2006;Zimmerman & Lahav, 2013) and the high number of babies who received ototoxic medications in the study population. In this study, treatment with ototoxic medications (when combined with other risk factors) was the most prevalent risk factor, and 3.9% of all hearing loss was associated with their use.…”
Section: Risk Factors In Isolationmentioning
confidence: 94%
“…Two risk factors were examined in isolation due to their high frequency of occurrence and known association or equivocal association with hearing loss. One of these factors was treatment with ototoxic medications due to the incongruous findings between hearing loss and ototoxic medications in previous studies (e.g., no association found by Hess et al, 1998, andSetiabudy et al, 2013; association found by Bielecki, Horbulewicz, & Wolan, 2011;Fuchs et al, 2016;Robertson, Tyebkhan, Peliowski, Etches, & Cheung, 2006;Zimmerman & Lahav, 2013) and the high number of babies who received ototoxic medications in the study population. In this study, treatment with ototoxic medications (when combined with other risk factors) was the most prevalent risk factor, and 3.9% of all hearing loss was associated with their use.…”
Section: Risk Factors In Isolationmentioning
confidence: 94%
“…Setiabudy et al [5] found no relationship between aminoglycosides serum trough concentration and ototoxicity in neonates with neonatal sepsis. Naeimiet et al [6] suggested that transient evoked otoacoustic emissions (TEOAEs) should be performed in neonatal intensive care unit (NICU) as routine for monitoring cochlear function to prevent permanent hearing loss especially in those who are receiving aminoglycoside for more than 7 days because TEOAEs is simple to perform, non-invasive, and reliable.…”
Section: Introductionmentioning
confidence: 98%
“…An adequate plasma level of amikacin is needed to kill the bacteria that cause sepsis. The target amikacin concentration for treating bacterial sepsis is 20-40 µg/ml, whereas the trough level to avoid nephrotoxicity is less than 10 µg/ml [3,4].…”
Section: Introductionmentioning
confidence: 99%